Aortic intimal sarcoma with abdominal metastasis: case report and management approach - Yao, Gongji; Xu, Jianwei (Frontiers in Oncology, 2025)
BackgroundAortic intimal sarcoma is an exceptionally rare malignancy with a poor prognosis. Tumors are predominantly located in the abdominal aorta, thoracic aorta, and thoracoabdominal aorta. Abdominal metastasis of aortic sarcoma is rarely documented, and effective treatment regimens are lacking.Case presentationA 55-year-old female presented with recurrent abdominal pain and a history of hypertension and mesenteric thrombosis. Initial arterial computed tomography angiography (CTA) revealed multiple thrombi with significant luminal narrowing, leading to a diagnosis of aortic thrombosis. She was referred to the First Affiliated Hospital of Zhejiang University for surgical intervention. Pathological analysis confirmed a diagnosis of aortic intimal sarcoma with MDM2 positivity. One month later, the patient developed severe abdominal pain, and positron emission tomography-computed tomography (PET-CT) showed accumulation in the small intestine, jejunum, and back muscles. Palliative tumor removal was performed, and the patient received chemotherapy with platinum drugs and epirubicin. Post-treatment PET-CT indicated no significant tumor staining or progression.DiscussionAortic intimal sarcoma is a rare neoplasm with limited treatment options. MDM2 overexpression is commonly observed, but similar histological features can appear in other conditions, making diagnosis challenging. Imaging modalities, including MRI and PET-CT, are crucial for diagnosis and monitoring. Current treatment strategies are non-standardized, but small-molecule inhibitors targeting MDM2 show promise. This case highlights the potential effectiveness of combined surgical and chemotherapeutic approaches for managing abdominal metastasis of aortic intimal sarcoma and provides a foundation for future clinical trials.